2013
DOI: 10.1615/jlongtermeffmedimplants.2013010100
|View full text |Cite
|
Sign up to set email alerts
|

Patient Activity after Total Hip Arthroplasty: A Comparison of Three Different Bearing Surfaces

Abstract: Patients who receive hip arthroplasty today desire prostheses that not only have great longevity, but are also suitable for a very active lifestyle. Advances in metallurgy, tribologic behavior, surgical technique, as well as improvements in strength and microstructure, have made ceramic-on-ceramic and metal-on-metal bearings available for young patients requiring a great deal of mobility. The purpose of this study was to assess if the bearing surface had an effect, if any, on postoperative activity levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Four articles had a mean UCLA score below 5.5 points and five articles above 7.5 points. Nine articles used similar scores (Tegner activity scale, Grimby scale, Lower Extremity Activity Scale (LEAS), Sports Activity Index, Weighted Activity Score) and their results are comparable to those of the studies using the UCLA [ 34 , 36 , 44 , 56 , 84 , 100 , 114 ].…”
Section: Resultsmentioning
confidence: 67%
“…Four articles had a mean UCLA score below 5.5 points and five articles above 7.5 points. Nine articles used similar scores (Tegner activity scale, Grimby scale, Lower Extremity Activity Scale (LEAS), Sports Activity Index, Weighted Activity Score) and their results are comparable to those of the studies using the UCLA [ 34 , 36 , 44 , 56 , 84 , 100 , 114 ].…”
Section: Resultsmentioning
confidence: 67%
“…The most common method for assessing satisfaction was the 10-point visual analog scale for satisfaction (7 studies, 29.2%). [20][21][22][23][24][25][26] Other methods included an ordinal scale (eg, very satisfied, satisfied, neutral, dissatisfied) (6 studies, 25.0%) [27][28][29][30][31][32] ; willingness to undergo surgery again (5 studies, 20.8%) 30,[32][33][34][35] ; and a binary scale (yes/ no for satisfied) (3 studies, 12.5%) (Table). [36][37][38] For the 3 studies reporting a binary (yes/no) result for patient satisfaction, all showed greater than 80% overall satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies examined satisfaction with the outcome of arthroplasty surgery (18 studies, 75.0%) 20,[22][23][24][25][26][27][28][29][30]32,[35][36][37][38][39][40][41] ; 2 studies (8.3%) examined satisfaction with cosmesis after THA 33,42 ; 3 studies (12.5%) considered satisfaction with the process of care 21,34,43 ; and 1 study evaluated satisfaction with physical therapy after THA. 31 Two studies (8.3%) measured satisfaction at multiple time points, 21,33 and the rest reported satisfaction only at 1 specific follow-up visit or at the final follow-up visit.…”
Section: Resultsmentioning
confidence: 99%
“…Today, younger and active patients need hip replacement in an attempt to restore the lost active lifestyle. MoMHR has been introduced to increase implant longevity and optimise the functional outcomes in this challenging patient group (26, 27). The present study has shown that good results are possible by non-designer surgeons, when indications and surgical technique are strictly respected.…”
Section: Discussionmentioning
confidence: 99%